ANALISIS SELF EFICCASY DG GEJALA KECEMASAN PADA PELAYAN MEDIS DI RS X - Yomima Viena S; Sandra Adetya; Faidah Ana Tasya (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The purpose of this research is to find out whether there is a relationship between self-efficacy and anxiety in nursing students. The subjects in this study were nursing students. The sampling technique used quota sampling and the sample in this study consisted of 102 nursing students. The measuring instrument used in this study uses an anxiety scale and a self-efficacy scale using a Likert scale. This study used the Spearman'Rho correlation test with a negative direction of -0.770 and a significance value of 0.000 (p <0.050). The results of this study can be said that there is a relationship between self-efficacy and anxiety in nursing students in facing final semester exams.